Quantity Surveying and its Association with Building Information Modeling (BIM) and Digital Twin (DT) (International Journal of Scientific Research and Management (IJSRM), 2024)
Quantity surveyors (QS) have many roles in the construction industry, and one of such roles is preparing bills of quantities that mainly entails taking measurements and pricing of construction work. They also develop schedule of project work, engage in construction project management, arbitration as well as dispute resolutions. Quantity take-off was their original role during 1820s when QS profession first came into existence. Critical observations brought criticisms that the profession would not survive if a tool could be developed that substituted QS roles in construction. Contingent to that criticism has seen the emergence of Building Information Modeling (BIM) that has specific attributes where the BIM technology can be used to quantify building works and produce schedule of works including cost loaded schedule in a 4D and 5D model interface respectively. Thus far, has the BIM technological innovation posed threats to the QS roles and/or to the profession? What of digital twin (DT)? The aim of this research was to investigate the QS and its association with BIM and DT innovation in the construction industry and to evaluate their future in the industry. Are they a bane or boon to the QS profession? Specific objectives were to determine the extent of BIM usage by QS, the level of the current usage and the future of QS considering BIM growth in the construction field. Strength, Weakness, Opportunity and Threat (SWOT) analysis was conducted about BIM usage. Survey questionnaire was administered to investigate the use of BIM and DT, current usage and future standing in construction. The results showed that BIM and DT were opportunities that added to the progress of QS. It was concluded that QS needed to embrace BIM technology more with integration of digital twins for full benefits in the construction industry.